A Comparison of Motivational Patterns in Sustainable Food Consumption between Pakistan and Finland: Duties or Self-Reliance?. Issue 5 (20th October 2021) - Rahman, Saleem ur; Luomala, Harri
Abstract: This research explores organic food consumption motivations in Pakistan and Finland. It links the findings to life goals typifying vertically collectivistic and horizontally individualistic cultures in order to produce a fuller understanding of cross-country variation in sustainable consumption. This study employs a means-end chain methodology, using a hard-laddering technique in Pakistan ( n = 101) and Finland ( n = 193) to collect the data. The key implications are that organic food choice motivations both converge and diverge between these countries and that culturally shaped life goals can be used to enrich their interpretation and advance theory building in further research.